2013
DOI: 10.3961/jpmph.2013.46.5.261
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic Characteristics and Leading Causes of Death Among the Casualties of Meteorological Events Compared With All-cause Deaths in Korea, 2000-2011

Abstract: ObjectivesThis study investigated the socio-demographic characteristics and medical causes of death among meteorological disaster casualties and compared them with deaths from all causes.MethodsBased on the death data provided by the National Statistical Office from 2000 to 2011, the authors analyzed the gender, age, and region of 709 casualties whose external causes were recorded as natural events (X330-X389). Exact matching was applied to compare between deaths from meteorological disasters and all deaths.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…This finding supports their increased vulnerability to lightning when indoors. Lee et al (2013) showed significant associations of lightning incidents with higher level of education (p=0.06) and occupation (p=0.001) (22). In the current study, higher level of education was associated with all three aspects: good knowledge (OR=1.9), favourable attitudes (OR=1.6) and satisfactory practices (OR=2.1).…”
Section: Discussionsupporting
confidence: 49%
“…This finding supports their increased vulnerability to lightning when indoors. Lee et al (2013) showed significant associations of lightning incidents with higher level of education (p=0.06) and occupation (p=0.001) (22). In the current study, higher level of education was associated with all three aspects: good knowledge (OR=1.9), favourable attitudes (OR=1.6) and satisfactory practices (OR=2.1).…”
Section: Discussionsupporting
confidence: 49%
“…Overall, 82% of them were published in international journals, while 18% were published in Korean domestic journals. As shown in Figure 4, 4 studies on the health effects of natural disasters [58,[87][88][89] were identified as of April 30, 2017, the studied health effects of which were death (n=2) [87,88], burden of disease (n =1) [58], and water-borne disease (n=1) [89]. Regarding the health impacts of UV exposure, although the major health effects of UV exposure were reported in the IPCC Fifth Assessment Report [1] as melanoma and eye disease, 4 of 5 studies conducted in Korea focused on the mental health outcome of UV exposure [80,81,90,91].…”
Section: Domain 3: Effects Of Other Climate Factors On Human Healthmentioning
confidence: 99%
“…The number of severe typhoons has increased in recent decades [2]. Typhoons affect tropical and subtropical zones and are often accompanied by high tides and heavy rain [3]. In Korea, typhoon warnings (Kyungbo) are issued when heavy widespread damage is expected due to the weather.…”
Section: Introductionmentioning
confidence: 99%